Quality of life, anxiety and depression symptoms in early and late pregnancy in women with pregestational diabetes. (1st December 2016) - Do, Nicoline C.; Secher, Anna L.; Cramon, Per; Ringholm, Lene; Watt, Torquil; Damm, Peter; Mathiesen, Elisabeth R.
Abstract: Introduction: The aim of this study was to explore changes in health‐related quality of life, anxiety and depression symptoms during pregnancy in women with pregestational diabetes. Material and methods: An observational cohort study including 137 pregnant women with pregestational diabetes (110 with type 1 and 27 with type 2). To evaluate changes from early to late pregnancy, the internationally validated questionnaires 36‐Item Short‐Form Health Survey (SF‐36) and Hospital Anxiety and Depression Scale (HADS) were completed at 8 and 33 gestational weeks. Results: From early to late pregnancy, the SF‐36 scales Physical Function, Role Physical, Bodily Pain and Physical Component Summary worsened ( p < 0.0001 for all scales). Physical Component Summary score deteriorated from mean 52.3 (SD 6.5) to 40.0 (9.7) ( p < 0.0001) and the deterioration was negatively associated with gestational weight gain in multiple linear regression (β = −0.34/kg, p = 0.03). The SF‐36 scale Mental Health improved ( p = 0.0009) and the Mental Component Summary score increased moderately from 47.6 (10.6) to 53.5 (8.6) ( p < 0.0001). Greater improvement in Mental Component Summary score was seen with lower HbA1c in late pregnancy. The HADS anxiety score improved slightly from 5.0 (3.3) to 4.5 (3.4) ( p = 0.04) whereas the HADS depression score remained unchanged. The prevalence of women with HADS anxiety or depression score ≥8 did not change. Conclusions: Physical quality of life deteriorated whereas mental quality of life improved slightly during pregnancy in women with pregestational diabetes. A minor reduction in anxiety and stable depression symptoms was observed. The results on mental health are reassuring, considering the great demands that pregnancy places on women with pregestational diabetes.